THE ROLE OF CORPUS LINGUISTICS IN LEARNING VOCABULARY (Journal of Universal Science Research, 2024)
This article examines the methods of teaching vocabulary using a corpus- based approach and also provides some data on how to employ a corpus-based approach in a teaching environment. Furthermore, it reveals some information about the reasons for using a corpus to teach vocabulary and its benefits.